2008
DOI: 10.1017/s0022215108002235
|View full text |Cite
|
Sign up to set email alerts
|

Causes of childhood deafness in Pukhtoonkhwa Province of Pakistan and the role of consanguinity

Abstract: Background: Deafness is the hidden disability of childhood, and leads to poor educational and employment prospects. There is little published information on deafness in Pakistan. Profound hearing impairment is more prevalent in countries where consanguineous marriages are common, such as Pakistan. This study aimed to assess causes of childhood deafness and association with parental consanguinity, within deaf and hearing children in the Peshawar district of Pukhtoonkhwa Province, Pakistan.Methods: One hundred a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 16 publications
1
21
0
Order By: Relevance
“…Consanguineous marriage is a custom that is commonly practiced among the African, Asian, and Latin American communities, whether they live in their own countries or are settled in USA or Europe. It is also common in Turkey, and many studies in Turkey and other countries have reported that the siblings of consanguineous marriages have a notably higher incidence of autosomal recessive diseases comprising hearing impairment [27][28][29][30][31] . Sajjad et al [28] conducted a study among 140 deaf school pupils and 221 non-hearing-impaired children in Pakistan.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consanguineous marriage is a custom that is commonly practiced among the African, Asian, and Latin American communities, whether they live in their own countries or are settled in USA or Europe. It is also common in Turkey, and many studies in Turkey and other countries have reported that the siblings of consanguineous marriages have a notably higher incidence of autosomal recessive diseases comprising hearing impairment [27][28][29][30][31] . Sajjad et al [28] conducted a study among 140 deaf school pupils and 221 non-hearing-impaired children in Pakistan.…”
Section: Discussionmentioning
confidence: 99%
“…It is also common in Turkey, and many studies in Turkey and other countries have reported that the siblings of consanguineous marriages have a notably higher incidence of autosomal recessive diseases comprising hearing impairment [27][28][29][30][31] . Sajjad et al [28] conducted a study among 140 deaf school pupils and 221 non-hearing-impaired children in Pakistan. They found that parental consanguinity (i.e., first and second cousins) constituted 86.4% of deaf school children and 59.7% of non-hearing-impaired children.…”
Section: Discussionmentioning
confidence: 99%
“…Various other studies conducted amongst children born to consanguineous parents reveal a much higher incidence of hearing loss in this group. 9,10,11 This study also reveals a family history of deafness in 22. 0%, this is supported by the study J.O.…”
Section: Discussionmentioning
confidence: 54%
“…Particularly in the Muslim community, 20-50 percent of all marriages are consanguineous. 11 The most recent consanguinity estimate indicated that some 10.4% of the world population are either married to a biological relative or are the progeny of a consanguineous union. There is no prescription that Muslims marry within the family, and first cousin marriage is freely permissible in the Jewish, Christian protestant, Buddhist and Zoroastrian / parsi religions.…”
Section: Introductionmentioning
confidence: 99%
“…Nonsyndromic deafness affects approximately 1 in 1000 newborns and 4% of people aged younger than 45 y (1). This number rises dramatically in regions where consanguinity is an acceptable social custom and is encouraged (2,3). Progressive HL affects an even greater proportion of the population.…”
Section: Hereditary Hearing Lossmentioning
confidence: 99%